Wyniki badań archeologicznych prowadzonych w 2018 roku w kruchcie Kościoła oo. Bernardynów w Rzeszowie - Jabłkowski, Michał (Muzeum Okręgowe w Rzeszowie, 2019)
Archaeological research conducted within the Basilica of the Assumption of the Blessed Virgin Mary in Rzeszów (Bernardine church) created a unique opportunity for interventional archaeological research, the first of this kind in the discused temple. In the course of studies, the remains of the church cemetery, which surrounded the former wooden church (existed on the site of today’s building) were recorded. Obtaining a collection of movable relics was a very important discovery, such as iron nails from coffins, pottery sherds and coins. Earthworks carried out in the church gave the opportunity to record the foundations of the porch, which was not mentioned in earlier literature. Thus, archaeological excavations in the church updated and expanded the information on the history of the monastery and the city of Rzeszów.

At the beginning of February 2018, in connection with the ongoing investment in the Basilica of Bernardine church in Rzeszów (the church of the Assumption of the Blessed Virgin Mary in Rzeszów) comprehensive archaeological works were conducted. They were performed by the Foundation for Archaeological Centre in Rzeszów. The excavations were carried out due to the fact that during the renovation of the church and the replacement of the floor, human remains and two crypts were found. It is worth noting that within the Bernardine church no archaeological research had been previously conducted, even in the form of keeping a watching brief. Two archaeological sondages (A and B) were established during the exploration of the porch. In the course of exploration of the first trial trench burial pits with human remains were discovered. At the 50–70 cm level, the only well-preserved skeleton in an anatomical order, oriented along the north-south line (grave 12) was registered. With reference to one of the burials deposited at 90–110 cm (grave 22), a coin was found. It was located under the skull of the deceased, adjacent to the jaw and leaving a characteristic greenish discoloration on the bone. The last level at which human burials were registered was the level of 110–130 cm. The graves revealed traces of destruction by other burials or reburials with a mixed context of human remains. The second trial trench, 1.5x0.5 m, in the form of a small test pit was studied at the southern, primary entrance to the church (sondage B). During the exploration, human bones were uncovered in a mixed context that did not form any clear clusters. By conservator’s decision, the boundaries of excavations were gradually expanded to reveal as much foundation as possible and, at the same time, confirm or refute the legend about the burial of the church founder under the threshold in the porch. According to historical sources, it was Mikołaj Spytek Ligęza, who wished (in his will written on August 7, 1637) to be buried under the threshold of the church porch. The results of the research did not confirm this legend. The movable material remains chronologically correspond to the 15th to 18th centuries. With regard to uncovered ceramic forms, pots dominated among pottery vessels. A fragment of a bowl and a plate were also noted. Similar forms of vessels were known from Rzeszów. Another group of artefacts were metals, including iron nails and coffin closing staples, as well as corroded lumps, wires and wheels difficult to identify, probably associated with the equipment and construction of coffins. In addition, a fragment of the iron horseshoe protector and two coins were discovered. To sum up, it is worth noting that archaeological research carried out within the Basilica of the Assumption of the Virgin Mary in Rzeszów created a unique opportunity for conducting archaeological intervention research. It brought a number of new and valuable information about the history of the city. In the course of excavations, archaeologists discovered the remains of a church cemetery, which undoubtedly surrounded the former wooden church existing on the site of the present building.
The results of archaeological research conducted in 2018 in the porch of the Bernardine church in Rzeszów
Keywords: urban archaeology; Rzeszów; Bernardine church; cemetery; burial; foundation